The Role of Circular Economy in Green Entrepreneurship: Sustainable Business Models - Rahim Munir; Rafika Fausiah (Cendekiawan Indonesia Timur, 2025)
The circular economy has emerged as a transformative framework for achieving sustainability in entrepreneurship by minimizing waste, optimizing resource use, and promoting regenerative business practices. Unlike the traditional linear economy that follows a